Achievement Sport Mapping Based on Evaluation of Koni Sports Development Program Using Context, Input, Process, Product (CIPP) Methods - Suratmin; I Putu Darmayasa; I Putu Panca Adi; I Ketut Sudiana; Ratna Kumala Setyaningrum; Hanik Liskustyawati (Universitas Pendidikan Ganesha, 2022)
The Provincial Sports Week (Porprov) organized by KONI in Bali Province showed unequal results, which were dominated by Badung Regency and Denpasar City. Related to this, KONI must have a clear and well-designed roadmap to lead sports coaching programs. It is important to map the achievement sports development program by the KONI of the Province of Bali so that sports coaching are carried out evenly and unevenly. The aim of the study was to evaluate the KONI sports development program in districts/cities in the province of Bali using the context, input, process, product (CIPP) model. Evaluation research uses an evaluation method with a qualitative approach supported by quantitative data. Data were obtained through participatory observation and interviews (athletes, coaches, questionnaires, archives and documentation). The research sample is 50 people. The sampling technique used was random sampling of district/city provincial KONI officials who were involved in the implementation of Porprov Bali. Data analysis used is data triangulation. The results of the study were in the form of (1) recommendations regarding the evaluation of district/city KONI sports achievement development programs in the province of Bali, (2) mapping of district/city KONI featured sports in the province. Bali, (3) district/city KONI policies in fostering achievement sports development, (4) relevant sports coaching models carried out by district/city KONI Bali province. The research results can be used as a basis for developing various policies to improve achievement in sports coaching, as well as a guide in mapping the development of regional leading sports.